Interested parties : the ideology of writers and readers of the Hebrew Bible - Clines, David J. A. (Journal for the study of the Old Testament. Supplement series, 1995)
One of the more creative Old Testament scholars of our time, David Clines offers an enjoyable and provocative set of studies on ideology. The title of a keynote essay, 'Why is There a Song of Songs, and What Does It Do to You If You Read It?', hints at the twin focus of the volume: the ideology of the writers, who bring the biblical texts into being, and the ideologies of the readers, who are shaped by the text at the same moment as they are shaping it in their own image. Among the essays are 'The Ten Commandments, Reading from Right to Left'; 'Metacommentating Amos'; 'David the Man: The Const.